THE INFLUENCE OF YOUTUBE VIDEOS ON LISTENING ACHIEVEMENT OF THE SECOND-GRADE STUDENTS AT MA GUPPI - Meldayanti; Indah Fadhilah Rahman; Kamsinah (Universitas islam Negeri Alauddin Makassar, 2022)
Listening skills have a significant part in learning English because receiving language input is a major skill that is important when learning a language. In addition, using YouTube videos are remarkable for enhancing the students’ listening achievements in the classroom. The research questions are: 1) how are the students’ listening achievements of the second grade students at MA Guppi Samata before learning listening using YouTube videos? 2) How are the students’ listening achievements of the second grade students at MA Guppi Samata after learning listening using YouTube videos? 3) Is there any significant difference of influence before and after using YouTube videos of the second grade at MA Guppi Samata? The design of the research was quantitative research which is pre-experimental research with one group pre-test and post-test design. The population was 50 students and the sample was chosen 25 students from XI B as the purposively. Tests were used as the instrument. All the collected data were analysed using the SPSS application showing all the students at MA Guppi Samata Gowa gained a 46.92 mean score, which convened as low classification in pre-test their first listening test. After some treatments, the mean score was increased 68.44 which classified as a reasonable classification. The degree of freedom (df) 24 pointed the students' listening achievement with t-test value (12.036) which turned out higher than the t-table value (2.064). This result analysis presented that this research's impact on the students effectively increased their scores and comprehension.